Myristic Acid Regulates Triglyceride Production in Bovine Mammary Epithelial Cells through the Ubiquitination Pathway - Mengxue Hu; Peifu Wu; Aiwei Guo; Lily Liu (Agriculture, 2023)
This study investigated the regulatory mechanism of myristic acid on milk fat synthesis in cows. An association between myristic acid and high milk fat content in Zhongdian yaks’ guts was found through combined metagenomic and metabolomic analysis. Bovine mammary epithelial cells (MAC-T) were cultured and treated with various myristic acid concentrations. After 24 h, the protein expression levels of CD36 (membrane glycoprotein CD36), ADFP (adipose differentiation-related protein), and UB (ubiquitin) were analyzed, along with cellular proteasome activity, triglyceride content, lipid droplets, and cell viability. Myristic acid at 200 μM significantly upregulated CD36, ADFP, UB, the content of triglyceride content and lipid droplets, and cell viability, but did not affect proteasome activity. Pathway analysis revealed that myristic acid regulates milk fat synthesis through ubiquitination–lysosome and ubiquitination–proteasome pathways. The study demonstrates myristic acid’s role in regulating triglyceride synthesis in MAC-T cells and its potential application as a feed additive for cattle, benefitting the dairy industry’s milk production efficiency and economic outcomes.